IMPLEMENTATION OF PRESIDENTIAL REGULATION NUMBER 83 OF 2018 CONCERNING HANDLING OF SEA WAS IN ORDER TO PROVIDE PROTECTION AND PRESERVATION OF THE SEA ENVIRONMENT FOR INDONESIA - Elly Kristiani Purwendah; Aniek Periani (Ganesha Law Review, 2019)
Countries are burdened with the obligation to prevent, reduce and control pollution of the marine environment caused by various sources. Countries can be held responsible for actions that cause pollution of the marine environment either intentionally or unintentionally because the State has an obligation to prevent activities that can cause pollution or damage to the environment in its territory and outside its jurisdiction. Based on existing data, plastic waste that can be produced in Indonesian waters reaches 1.65 million tons / year. Research data has outlined the distribution of plastic waste in several countries, one of which is Indonesia. In the survey conducted, Indonesia was the second country after China with a high amount of plastic waste not managed well. The Government of Indonesia has issued Presidential Regulation No. 83 of 2018, on handling marine waste, and contains the National Action Plan 2018-2025 involving various Ministries / Institutions and Local Governments. As the host of the Our Ocean Conference 2018 meeting, out of 22 Commitments delivered by Indonesia, 5 of them were commitments related to efforts to tackle plastic waste at sea. Implementation of Presidential Regulation Number 8 of 2018 is important to be carried out to overcome marine waste in Indonesia, besides that the application of this Presidential Regulation will prove Indonesia's commitment in the eyes of the international world in keeping the sea healthy. Not only in making rules, but also in the concrete steps of the rules.